Reclaiming Sacrifice: Integrating Girardian and Feminist Insights on the Cross - King, Chelsea Jordan (Springer International Publishing, 2024)
Chapter 1: Saved by an Innocent Death? -- Chapter 2: Feminist and Womanist Critiques of the Cross as Sacrifice -- Chapter 3: Girard and the Non-Sacrificial Reading of the Gospels.-Chapter 4: A Change of Heart -- Chapter 5: Reclaiming Sacrifice.